Case Report: Neurolymphomatosis of the peripheral nerve as a presentation of relapsed pediatric high-grade B cell lymphoma - Lu, Evelyn Ruoyun; Yeung, Wai Lan; Yau, Jeffrey Ping Wa; Chu, King Sun; Kan, Elaine Yee Ling; Chiang, Alan Kwok Shing (Frontiers in Oncology, 2025)
Neurolymphomatosis (NL) of the peripheral nerve in pediatrics has never been reported, and ultrasonography (USG) as an investigation modality is rarely used. We report a case of an 11-year-old boy with stage 4 mature high-grade B cell lymphoma who presented with a two-week history of right ulnar neuropathy and left sciatic neuropathy one month after the completion of frontline chemotherapy. This case report illustrates the rare presentation of NL in lymphoma relapse and hopes to emphasize how early identification of this diagnosis and timely treatment are essential. Moreover, this case points out how USG, in the context of palpable mass and localized neurological signs, could facilitate a diagnosis of NL.